High-density insensitive energetic materials: 2, 4, 6-tris(2-fluoro-2, 2-dinitroethoxy)-1, 3, 5-triazine. Issue 106 (1st November 2016) - Gidaspov, Alexander A.; Bakharev, Vladimir V.; Suponitsky, Kyrill Yu.; Nikitin, Valery G.; Sheremetev, Aleksei B.
Abstract : A Na3 PO4 -promoted nucleophilic substitution of all chlorine atoms of cyanuric with fluorodinitroethanol was achieved with excellent yield. The product demonstrates promising potential for diverse applications like explosives or propellants. Abstract : An efficient and reliable synthesis of 2, 4, 6-tris(2-fluoro-2, 2-dinitroethoxy)-1, 3, 5-triazine (1 ) has been developed. The ether1 was fully characterized by IR and multinuclear NMR spectroscopy, and X-ray crystal structure determinations. The compound exhibits good density, excellent thermal stability, and high performance, while impact sensitivities are comparable to TNT.